Identification of Quantitative Trait Loci Controlling the Development of Prickles in Eggplant by Genome Re-sequencing Analysis - Qian, Zongwei; Zhang, Bin; Chen, Haili; Lu, Lei; Duan, Mengqi; Zhou, Jun; Cui, Yanling; Li, Dayong (Frontiers in Plant Science, 2021)
Eggplant (Solanum melongena L.) is the third most important crop in the family of Solanaceae. Prickles are considered as the undesirable traits during eggplant planting and fruits transportation. The mechanism of prickles development has been not clear in eggplant. Here, we constructed a high-quality genetic linkage Bin map derived from re-sequencing analysis on a cross of a prickly wild landrace, 17C01, and a cultivated variety, 17C02. The major QTL controlling the evelopment of prickles on the calyx (explained 30.42% of the phenotypic variation), named as qPC.12, was identified on a ~7 kb region on chromosome 12. A gene within qPC.12, that encodes a WUSCHEL-related homeobox like protein, with higher expression levels in 17C01 calyx and 22 bp deletion in 17C02 was probably the functional gene for prickle formation. Results from this study will ultimately facilitate uncovering the molecular regulatory mechanisms underlying the development of prickle in eggplant.